Intelligent computing and internet of things. first International Conference on Intelligent Manufacturing and Internet of Things and 5th International Conference on Computing and Sustainable Energy and Environment, IMIOT and ICSEE 2018, Chongqing, China, September 21-23, 2018 proceedings /: first International Conference on Intelligent Manufacturing and Internet of Things and 5th International Conference on Computing and Sustainable Energy and Environment, IMIOT and ICSEE 2018, Chongqing, China, September 21-23, 2018 proceedings. Part II : (2018) - Unknown
No abstract available